2019
DOI: 10.4274/eajem.galenos.2018.93723
|View full text |Cite
|
Sign up to set email alerts
|

Are the Judicial Reports Prepared in Emergency Services Consistent with Those Prepared in Forensic Medicine Department of a University Hospital?

Abstract: Aim:This study aimed to analyze the judicial reports prepared in emergency services and to emphasize the importance of forensic medicine education for the physicians working at these services and the reflection of the situation to the judicial authorities. Materials and Methods:Reports prepared by Forensic Medicine Department of Gaziantep University Medical Faculty were accepted as the gold standard and the judicial reports of the same patients prepared in emergency services were compared retrospectively.Resul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 14 publications
1
1
0
Order By: Relevance
“…Considering the nature of forensic events, we see that traffic accidents ranked first with 33.3%, followed by assault and battery cases with 24.1% and occupational accidents with 21.5%. In our study, it was found that physicians kept forensic reports mostly related to traffic accidents, which was consistent with similar studies in the literature 2,25,26,29,[31][32][33] . In addition to the fact that traffic accidents and related injuries are still a major problem in our country, it was associated with the fact that our hospital was located close to the city center and intercity road junction.…”
Section: Resultssupporting
confidence: 92%
“…Considering the nature of forensic events, we see that traffic accidents ranked first with 33.3%, followed by assault and battery cases with 24.1% and occupational accidents with 21.5%. In our study, it was found that physicians kept forensic reports mostly related to traffic accidents, which was consistent with similar studies in the literature 2,25,26,29,[31][32][33] . In addition to the fact that traffic accidents and related injuries are still a major problem in our country, it was associated with the fact that our hospital was located close to the city center and intercity road junction.…”
Section: Resultssupporting
confidence: 92%
“…Besides, the physician must be unbiased while drafting the MLR. 13 However, significant numbers of physicians do not understand their responsibility in writing MLRs, and therefore, there is a need to train physicians in writing MLRs. 14 In a study conducted in Egypt, 67.1% of the physicians reported difficulty in writing MLRs.…”
Section: Discussionmentioning
confidence: 99%